Differences of mentally ill patients' satisfaction degree during their involuntary or voluntary stay in a psychiatric clinic - Aspasia Goula; Evaggelos Margetis; Maria-Aggeliki Stamouli; Dimitra Latsou; Vasiliki Gkioka (SAGE Publishing, 2021)
Background: Mental health illness is not considered as a private matter, as it affects not only the mental patient's life and those who are considered his/her immediate family, but also the society as a whole. The involuntary examination and/or hospitalization in the field of mental health as the basic first-line therapeutic solution in Greece, calls for an immediate intervention, which is supposed to counterbalance the need for therapy and patient's rights of personal freedom and safety. Design and methods: A research using questionnaire was realized, consisting of 100 hospitalized patients in psychiatric clinics (50 voluntarily and 50 involuntarily hospitalized) at the Psychiatric Hospital of Attica. The sampling scheme was the stratified sampling and the level of statistical significance was set to α=0.05. Results: The results have shown that involuntarily and voluntarily hospitalized mental patients did not differ significantly with almost the entirety of the questionnaire; however, the involuntary patients were significantly more satisfied with the conditions of hospitalization as well as assessing the overall quality of the services provided during their hospitalization. Conclusions: For mentally ill patients, greater importance and stronger correlation with gratification, does not constitute the admission procedure to the psychiatric clinic but the development of effective communication and therapeutic relationship with the staff, full knowledge and update about patient's health condition, medication, participation in therapeutic planning and hospitalization in a regime of autonomy and respect for their rights.